뇌졸중으로 인한 편마비 환자의 보행평가를 위한 체중심 가속도센서 기반의 새로운 보 검출 알고리즘 개발 - 이효기; 황성재; 조성필; 이동률; 유승현; 이경중; 김영호; 정하중; Lee, Hyo-Ki; Hwang, Sung-Jae; Cho, Sung-Pil; Lee, Dong-Ryul; et al. (Journal of biomedical engineering research, 2009)
In this study, we have developed a novel step detection algorithm for gait evaluation of patients with hemiplegia based on trunk accelerometry device. For this, we have used a bandpass filter and a least square acceleration (LSA) filter which is characterized by emphasizing the peak or valley point of the acceleration signals for each 3-axis accelerometer signals. To evaluate the algorithm, the detected steps by developed algorithm and real steps by the motion analysis system were compared. As a result, we could obtain the sensitivity of 96.44%, the specificity of 99.94% and the accuracy of 99.90% for the patients' data sets and the sensitivity of 100%, the specificity of 99.93% and the accuracy of 99.93% for the normal data sets. In conclusion, the developed algorithm is useful for the step detection for patients with hemiplegia as well as normal subjects.